Positive electrode active material, method for preparing same, and positive electrode and lithium secondary battery comprising same
By uniformly distributing the porosity in the Li and Mn-rich positive electrode active material, the problems of high resistance and low thermal stability of lithium secondary batteries during charging/discharging are solved, and better capacity and life characteristics are achieved.
Patent Information
- Application Number
- CN202480004954.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-30
- Filing Date
- 2024-01-30
- Publication Date
- 2025-06-27
AI Technical Summary
The positive electrode active materials of existing lithium secondary batteries have high resistance and low thermal stability during charging/discharging, resulting in poor capacity and life characteristics.
A Li and Mn-rich positive electrode active material has a uniformly distributed porosity on the surface, and a uniform distribution of pores is ensured by a specific preparation method including a co-precipitation reaction and a firing process.
Through uniformly distributed porosity, the mobility of lithium ions is improved, the resistance is reduced, and the capacity and life characteristics are enhanced.
Smart Images

Figure CN120226165A_ABST
Abstract
Description
Technical Field
[0001] [Cross - reference to Related Applications]
[0002] This application claims the benefit of priority of Korean Patent Application No. 10 - 2023 - 0011790, filed with the Korean Intellectual Property Office on January 30, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present invention relates to a positive electrode active material, a method for preparing the same, a positive electrode including the same, and a lithium secondary battery, and the positive electrode active material has improved resistance characteristics and life characteristics. Background Art
[0004] With the technological development and increasing demand of mobile devices, the demand for secondary batteries as an energy source has increased rapidly. Among these secondary batteries, lithium secondary batteries with high energy density, high voltage, long cycle life, and low self - discharge rate have been commercialized and widely used.
[0005] Lithium transition metal composite oxides have been used as positive electrode active materials for lithium secondary batteries. In particular, lithium cobalt composite metal oxides such as LiCoO2 with high working voltage and excellent capacity characteristics have been mainly used. However, LiCoO2 has very poor thermal performance due to the unstable crystal structure caused by de - lithiumation, and it is also expensive, so it has limitations in being widely used as a power source in fields such as electric vehicles.
[0006] Lithium manganese composite metal oxides (LiMnO2 or LiMn2O4), lithium iron phosphate compounds (LiFePO4, etc.), or lithium nickel composite metal oxides (LiNiO2, etc.) have been developed as materials to replace LiCoO2. Among these materials, lithium nickel composite metal oxides have been more actively studied and developed, and large - capacity batteries can be easily realized due to their high reversible capacity of about 250 mAh / g. However, the thermal stability of LiNiO2 is worse than that of LiCoO2, and when an internal short - circuit occurs due to external pressure in the charged state, the positive electrode active material itself decomposes, resulting in battery rupture and fire.
[0007] Therefore, as a method for maintaining the excellent reversible capacity of LiNiO2 and improving its low thermal stability, nickel - cobalt - manganese - based lithium composite metal oxides (hereinafter, simply referred to as "NCM - based lithium composite transition metal oxides") in which a part of Ni is replaced by Mn and Co or Al have been developed.
[0008] However, due to the recent increase in the price of cobalt (Co), a lithium-rich (Li-rich) NCM-based cathode active material that can meet high capacity while having a relatively low cobalt (Co) content or no cobalt (Co) has been developed.
[0009] On the other hand, compared with conventional NCM-based cathode active materials, a cobalt-free, Li-rich, and Mn-rich cathode active material requires a large amount of Li in the process of firing a precursor and a lithium raw material to obtain the cathode active material. Therefore, a cathode active material precursor with a high specific surface area that can contact Li is required, and when pores do not exist or pores only exist inside the precursor, the battery characteristics deteriorate.
[0010] Therefore, it is necessary to develop a cathode active material in which pores are uniformly distributed on its inner and outer surfaces and which thus exhibits excellent battery characteristics.
[0011] [Prior Art Documents]
[0012] [Patent Documents]
[0013] (Patent Document 1) CN 110112388 A (August 9, 2019) Summary of the Invention
[0014] Technical Problem
[0015] To solve the above problems, an aspect of the present invention provides a cathode active material having a defined porosity on its surface portion in a Li-rich and Mn-rich cathode active material.
[0016] Another aspect of the present invention provides a method for preparing a cathode active material.
[0017] Another aspect of the present invention provides a cathode and a lithium secondary battery including the cathode active material.
[0018] Technical Solution
[0019] To solve the above problems, the present invention provides a cathode active material, a method for preparing the same, and a cathode and a lithium secondary battery including the same.
[0020] (1) According to an aspect of the present invention, there is provided a cathode active material represented by the following Chemical Formula 1 and formed of polycrystalline particles, the polycrystalline particles being composed of secondary particles in which primary particles are aggregated, wherein the surface porosity A defined by the following Mathematical Formula 1 is 1% to 30%.
[0021] [Chemical Formula 1]
[0022] x[LiMn p Ni (1-p-q-r) Co q M1 r O2]·(1 - x)[Li2Mn s M 2 (1-s) O3]
[0023] In the above Chemical Formula 1,
[0024] M 1 and M 2 are each independently one selected from Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na, and Pt, and
[0025] satisfy 0.500 < x < 0.800, 0.450 < p < 0.650, 0 ≤ q ≤ 0.025, 0 ≤ r ≤ 0.100, 0.900 ≤ s ≤ 1.000,
[0026] [Mathematical Formula 1]
[0027] A(%) = [P A / S A × 100
[0028] In the above Mathematical Formula 1,
[0029] P A represents the area ratio of the pores in the surface part on the cross-section of the positive electrode active material,
[0030] S A is the area ratio of the surface part on the cross-section of the positive electrode active material,
[0031] The inside of the cross-section of the positive electrode active material is the region formed by connecting the points at half the distance from the center to the outermost surface on the cross-section of the positive electrode active material, and
[0032] The surface part on the cross-section of the positive electrode active material is the region other than the inside.
[0033] (2) The present invention provides the positive electrode active material according to the above (1), wherein the surface part porosity A is 2% to 20%.
[0034] (3) The present invention provides the positive electrode active material according to the above (1) or (2), wherein the positive electrode active material does not contain Co.
[0035] (4) The present invention provides the positive electrode active material according to any one of the above (1) to (3), wherein the positive electrode active material is represented by the following Chemical Formula 1-1.
[0036] [Chemical Formula 1-1]
[0037] x[LiMnp Ni (1-p-r) M 1 r O2]·(1-x)[Li2Mn s M 2 (1-s) O3]
[0038] In the above chemical formula 1-1,
[0039] M 1 and M 2 are each independently one selected from Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na, and Pt, and
[0040] satisfy 0.55 < x < 0.70, 0.52 < p < 0.58, 0 ≤ r ≤ 0.10, 0.90 ≤ s ≤ 1.00.
[0041] (5) The present invention provides a positive electrode active material according to any one of the above (1) to (4), wherein the average particle diameter D of the positive electrode active material 50 is 3 μm to 12 μm.
[0042] (6) According to another aspect of the present invention, there is provided a method for preparing a positive electrode active material represented by the following chemical formula 1 according to any one of the above (1) to (5), the method comprising: mixing a transition metal hydroxide and a lithium raw material and firing,
[0043] wherein the transition metal hydroxide is prepared by the following steps:
[0044] Forming an inert atmosphere with a pH of 12 to 13 inside the reactor (S1),
[0045] Injecting nitrogen and air with a volume ratio of 99.5:0.5 to 85.0:15.0 into the reactor to form an active atmosphere, adding a transition metal solution containing Ni and Mn, and an alkaline solution, and subjecting the mixture to a coprecipitation reaction under the condition of a pH of 10 to 11 (S2).
[0046] [Chemical formula 1]
[0047] x[LiMn p Ni (1-p-q-r) Co q M 1 r O2]·(1-x)[Li2Mn s M 2 (1-s) O3]
[0048] In the above chemical formula 1,
[0049] M 1 and M 2 each independently is one selected from Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na, and Pt, and
[0050] satisfies 0.500 < x < 0.800, 0.450 < p < 0.650, 0 ≤ q ≤ 0.025, 0 ≤ r ≤ 0.100, 0.900 ≤ s ≤ 1.000.
[0051] (7) The present invention provides the method according to (6) above, wherein step (S1) is carried out by the following steps: adding a solvent and an alkaline solution to a reactor and mixing them to form an atmosphere with a pH of 12 to 13, and then introducing an inert gas.
[0052] (8) The present invention provides the method according to (6) or (7) above, wherein in step (S2), the coprecipitation reaction is carried out by the following steps:
[0053] adding an alkaline solution within 1 to 2 hours after adding the transition metal solution to the reactor to make the pH in the reactor reach 10 to 11 to initiate the reaction, and
[0054] continuing the reaction for 20 to 50 hours while maintaining the pH at 10 to 11.
[0055] (9) The present invention provides the method according to any one of (6) to (8) above, wherein the content of Mn in the transition metal of the transition metal hydroxide is 50 mol% or more.
[0056] (10) The present invention provides the method according to any one of (6) to (9) above, wherein the transition metal hydroxide does not contain Co.
[0057] (11) The present invention provides the method according to any one of (6) to (10) above, wherein the transition metal hydroxide is mixed with a lithium raw material such that the lithium element in the transition metal hydroxide and the lithium raw material is present in a molar ratio of 1:1.2 to 1:1.6.
[0058] (12) According to another aspect of the present invention, there is provided a positive electrode, the positive electrode comprising:
[0059] a current collector, and
[0060] a positive electrode active material layer provided on at least one surface of the current collector,
[0061] wherein the positive electrode active material layer comprises the positive electrode active material according to any one of (1) to (5) above.
[0062] (13) According to another aspect of the present invention, there is provided a lithium secondary battery, comprising:
[0063] the positive electrode described in the above (12),
[0064] a negative electrode,
[0065] a separator disposed between the positive electrode and the negative electrode, and
[0066] an electrolyte.
[0067] Advantageous Effects
[0068] The positive electrode active material according to the present invention has pores uniformly distributed both in the interior and on the surface portion, so that even as a positive electrode active material rich in Li and Mn, lithium ions can easily move during charging / discharging, resulting in reduced resistance and excellent capacity characteristics and life characteristics.
[0069] The method for preparing a positive electrode active material according to the present invention involves coprecipitating transition metals in an active atmosphere adjusted to a weak oxygen atmosphere to prepare a transition metal hydroxide, mixing the transition metal hydroxide with a lithium raw material and firing, thereby preparing a positive electrode active material having surface portion pore characteristics under specific conditions.
[0070] In addition, the positive electrode and the lithium secondary battery according to the present invention contain the above positive electrode active material, and thus have excellent capacity characteristics and life characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] The following attached drawings herein illustrate preferred examples of the present invention by way of example, and are used together with the following specific embodiments of the present invention to further understand the technical concept of the present invention. Therefore, the present invention should not be construed only based on the content in these drawings.
[0072] Figure 1 SEM image of the positive electrode active material prepared in Example 1 (at a magnification of 20K);
[0073] Figure 2 SEM image of the positive electrode active material prepared in Example 2 (at a magnification of 20K);
[0074] Figure 3 SEM image of the positive electrode active material of Example 3 (at a magnification of 20K);
[0075] Figure 4 SEM image of the positive electrode active material of Comparative Example 1 (at a magnification of 20K);
[0076] Figure 5SEM image of the positive electrode active material of Comparative Example 2 (at a magnification of 20K);
[0077] Figure 6 SEM image of the positive electrode active material of Comparative Example 3 (at a magnification of 20K);
[0078] Figure 7 is an image showing the measurement process of the surface porosity of the positive electrode active material according to an embodiment of the present invention, showing the following process:
[0079] (a) The process of selecting particles on a cross-section, distinguishing particle contours and unnecessary backgrounds, and removing the backgrounds,
[0080] (b) The process of distinguishing the inside and surface part of the particles,
[0081] (c) and (d) The process of obtaining the area ratio (A1) occupied by the surface part excluding pores and the area ratio (A2) excluding pores in the surface part with respect to the total area of the image using Image J. Detailed Description
[0082] It should be understood that the words or terms used in the description and claims of the present invention should not be construed as being limited to the meanings defined in a general dictionary. It should also be understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to best explain the present invention, the words or terms should be construed as having meanings consistent with their meanings in the context of the relevant technical field and the technical gist of the present invention.
[0083] Definition of Terms
[0084] As used herein, the term "polycrystalline particle" refers to a particle having a morphology in which the lattice structure aggregates in an irregular orientation throughout the particle, and may be composed of secondary particles in which primary particles are agglomerated. As used herein, a secondary particle has a structure in which small-sized primary particles are physically and / or chemically agglomerated to form a relatively large particle, which is generally a particle structure in contrast to the primary particle.
[0085] As used herein, the term "porosity (%)" represents the percentage of pore space in a particle, representing the ratio of the area occupied by pores to a reference area.
[0086] Measurement Method
[0087] In this text, a cross-section of the positive electrode active material was obtained using SEM (Quanta FEG 250, manufactured by PHILIPS) under the following conditions. Particles on the cross-section (Figure 7(a)) were selected to obtain the particle contour, and unnecessary background parts were removed, and the inner and surface parts were distinguished (Figure 7(b)). Then, the surface porosity A was measured using the image processing program ImageJ. In this case, the inner part of the cross-section is the region formed by connecting the points at a distance of 1 / 2 from the center of the positive electrode active material cross-section to the outermost surface of the positive electrode active material cross-section (see Figure 7(b)).
[0088] High voltage: 10,000 kV
[0089] Chamber pressure: 9.0×10 -5 mbar
[0090] Gun pressure: 6.85×10 -10 mbar
[0091] Emission current: 165 μA
[0092] WD: 10 mm
[0093] Beam spot size: 3.0
[0094] Stage bias voltage: 4000 V
[0095] Using ImageJ, the area ratio (A1) occupied by the surface part excluding pores with respect to the total area of the image and the area ratio (A2) excluding the pores in the surface part with respect to the total area of the image were obtained (Figure 7(c) and (d)). The area ratio of the pores in the surface part (P A ) was obtained by subtracting the area ratio of the part excluding the pores in the surface part (A2) (100 - A2) from the total area (100), and the area ratio of the surface part (S A ) was calculated by adding the area ratio (A1) occupied by the surface part and the area ratio of the pores in the surface part (P A ).
[0096] Thereafter, the surface porosity was calculated by the following Mathematical Formula 1.
[0097] [Mathematical Formula 1]
[0098] A(%) = [P A / S A × 100
[0099] In the above Mathematical Formula 1,
[0100] P A represents the area ratio of the pores in the surface part of the positive electrode active material cross-section,
[0101] SA Represents the area ratio of the surface part on the cross-section of the positive electrode active material. The interior of the cross-section of the positive electrode active material is a region formed by connecting points at a distance of 1 / 2 from the center to the outermost surface on the cross-section of the positive electrode active material, and the surface part on the cross-section of the positive electrode active material is the region other than the interior.
[0102] As another example, in terms of obtaining a value with higher precision, using SEM (Quanta FEG 250, PHILIPS), the cross-section of the positive electrode active material can be obtained. 30 particles can be selected from this cross-section, and the area ratio P of the pores in the surface part of each of the 30 particles can be obtained through the above process. Ai (where i is an integer from 1 to 30) and the area ratio S of the surface part Ai (where i is an integer from 1 to 30), and the surface part porosity A of the 30 particles can be obtained through the above mathematical formula 1. i (where i is an integer from 1 to 30), and then its average value can be provided as the surface part porosity A' (see the following mathematical formula 2).
[0103] [Mathematical formula 2]
[0104]
[0105] (where n is the integer 30)
[0106] On the other hand, the standard deviation of the surface part porosity A and the surface part porosity A' is 2 or less.
[0107] Hereinafter, the present invention will be described in detail.
[0108] Positive Electrode Active Material
[0109] The present invention provides a Li- and Mn-rich positive electrode active material having uniformly distributed pores in the interior and surface part, particularly having specific pore characteristics on the surface part, thereby facilitating the movement of lithium ions during charge / discharge.
[0110] The positive electrode active material according to an embodiment of the present invention is represented by the following chemical formula 1 and is formed of polycrystalline particles, and the polycrystalline particles are composed of secondary particles in which primary particles are aggregated. The surface part porosity A defined by the following mathematical formula 1 is 1% to 30%.
[0111] [Chemical formula 1]
[0112] x[LiMn p Ni (1-p-q-r) Co q M 1 rO2]·(1 - x)[Li2Mn s M 2 (1-s) O3]
[0113] In the above Chemical Formula 1,
[0114] M 1 and M 2 are each independently one selected from Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na, and Pt, and
[0115] 0.500 < x < 0.800, 0.450 < p < 0.650, 0 ≤ q ≤ 0.025, 0 ≤ r ≤ 0.100, 0.900 ≤ s ≤ 1.000 are satisfied.
[0116] [Mathematical Formula 1]
[0117] A(%) = [P A / S A × 100
[0118] In the above Mathematical Formula 1,
[0119] P A represents the area ratio of pores in the surface part of the cross-section of the positive electrode active material,
[0120] S A is the area ratio of the surface part of the cross-section of the positive electrode active material, and
[0121] the inside of the cross-section of the positive electrode active material is a region formed by connecting points at a distance of 1 / 2 from the center to the outermost surface of the cross-section of the positive electrode active material, and the surface part of the cross-section of the positive electrode active material is the region other than the inside.
[0122] Specifically, the surface part porosity A of the positive electrode active material according to an embodiment of the present invention can be 2% to 20%.
[0123] Typical NCM-based positive electrode active materials are prepared from precursors having a single-phase rhombohedral lattice structure and have a structure in which transition metal layers and Li layers are repeated.
[0124] On the other hand, a cobalt-free or cobalt-containing rich Li and Mn cathode active material can be prepared from a Mn-rich precursor having a crystal structure of a monoclinic lattice and a trigonal lattice two-phase, and having a structure in which Li atoms are further included in the transition metal layer in addition to the repeating structure of the transition metal layer and the Li layer. Therefore, compared with conventional NCM-based cathode active materials, a large amount of Li is required when obtaining the cathode active material by mixing the precursor with a lithium raw material and firing, and thus a cathode active material precursor with a high specific surface area in contact with Li is required. In this case, when pores are unevenly distributed in the interior and surface portion of the precursor and only exist in the interior, the prepared cathode active material has no pores in its surface portion, resulting in interruption of the movement of lithium ions during charge / discharge and poor battery characteristics.
[0125] However, the cathode active material according to the present invention is a rich Li and Mn (over-lithiated and manganese-based) cathode active material and has a porosity defined under specific conditions in the surface portion, thereby facilitating the movement of lithium ions during charge / discharge and resulting in excellent capacity characteristics and life characteristics.
[0126] On the other hand, the surface portion porosity A may be the average value of the polycrystalline grains forming all or part of the cathode active material, or may be a value satisfied by 70% or more of the polycrystalline grains forming the cathode active material.
[0127] As an example, 30 polycrystalline grains forming the cathode active material can be randomly selected, the surface portion porosity can be obtained from the cross-section of each grain, and the range of the surface portion porosity A can be defined as its average value.
[0128] As another example, the surface portion porosity of each polycrystalline grain forming the cathode active material can be obtained, and the range of the surface portion porosity A can be defined as the range satisfied by 70% or more of the polycrystalline grains.
[0129] The cathode active material according to an embodiment of the present invention is a lithium composite transition metal oxide containing Ni and Mn, and the content of Mn may be 50 mol% or more relative to the transition metal other than lithium. In this case, a high capacity of the cathode active material can be easily obtained.
[0130] As another example, in terms of balancing excellent initial charge / discharge capacity, the content of Mn in the transition metal may be 55 mol% to 80 mol%, specifically 60 mol% to 80 mol%.
[0131] As another example, the cathode active material may not contain Co.
[0132] More specifically, the cathode active material according to an embodiment of the present invention can be represented by the following Chemical Formula 1.
[0133] [Chemical Formula 1]
[0134] x[LiMn p Ni (1-p-q-r) Co q M 1 r O2]·(1 - x)[Li2Mn s M 2 (1-s) O3]
[0135] In the above Chemical Formula 1,
[0136] M 1 and M 2 are each independently one selected from Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na, and Pt, and
[0137] satisfy 0.500 < x < 0.800, 0.450 < p < 0.650, 0 ≤ q ≤ 0.025, 0 ≤ r ≤ 0.100, 0.900 ≤ s ≤ 1.000.
[0138] Specifically, in the positive electrode active material, the content of Li can correspond to (2 - x). Specifically, (2 - x) can be 1.10 to 1.30 or 1.13 to 1.21. When (2 - x) is within the above range, excellent initial capacity can be achieved without worrying about the difficulty in forming an over-lithiated manganese phase structure due to the generation of a secondary phase and thus a decrease in capacity, and an increase in gas generation and thus a decrease in discharge capacity due to an increase in lithium by-products.
[0139] In addition, in the positive electrode active material, the content of Mn can correspond to [xp + (1 - x)s], and when [xp + (1 - x)s] is within the above range, the charge capacity can be excellent.
[0140] In addition, in the positive electrode active material, the content of Ni can correspond to x(1 - p - q - r), and when x(1 - p - q - r) is within the above range, the charge capacity can be excellent.
[0141] In addition, in the positive electrode active material, M 1 and M 2 can each be a doping element contained in the crystal structure of the positive electrode active material, and the content can correspond to xr + (1 - x)(1 - s), and M 1 and M 2 can be the same or different.
[0142] More specifically, the positive electrode active material can be represented by the following Chemical Formula 1-1.
[0143] [Chemical Formula 1-1]
[0144] x[LiMn p Ni (1-p-r) M 1 r O2]·(1-x)[Li2Mn s M 2 (1-s) O3]
[0145] In the above Chemical Formula 1-1,
[0146] M 1 and M 2 are each independently one selected from Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na, and Pt, and
[0147] satisfy 0.55 < x < 0.70, 0.52 < p < 0.58, 0 ≤ r ≤ 0.10, 0.90 ≤ s ≤ 1.00.
[0148] As another example, the average particle diameter D of the positive electrode active material 50 can be 3 μm to 12 μm, specifically 5 μm to 10 μm or 6 μm to 8 μm.
[0149] In addition, the total porosity of the positive electrode active material can be 1% to 30%, and the difference between the internal porosity and the surface porosity can be 1% to 30%. Specifically, the total porosity can be 5% to 20%, and the difference between the internal porosity and the surface porosity can be 7% to 20%, and the internal porosity can be greater than the surface porosity. In this case, the pores are uniformly distributed throughout the positive electrode active material, whereby lithium migration can be further facilitated during charging / discharging, resulting in better battery characteristics.
[0150] Method for Preparing Positive Electrode Active Material
[0151] The present invention provides a method for preparing a positive electrode active material, which can prepare a positive electrode active material.
[0152] The method for preparing the positive electrode active material represented by the above Chemical Formula 1 according to an embodiment of the present invention includes: mixing a transition metal hydroxide and a lithium raw material and firing them,
[0153] In this case, the transition metal hydroxide is prepared through the following steps:
[0154] Forming an inert atmosphere with a pH of 12 to 13 inside the reactor (S1),
[0155] Inject nitrogen and air with a volume ratio of 99.5:0.5 to 85.0:15.0 into the reactor to form an active atmosphere, add a transition metal solution containing Ni and Mn, and an alkaline solution, and carry out a coprecipitation reaction (S2) on the mixture under the condition that the pH is 10 to 11.
[0156] The lithium raw material can be a lithium-containing carbonate (e.g., lithium carbonate), hydrate (e.g., lithium hydroxide hydrate (LiOH·H2O), etc.), hydroxide (e.g., lithium hydroxide, etc.), nitrate (e.g., lithium nitrate (LiNO3), etc.), and chloride (e.g., lithium chloride (LiCl), etc.), and any one of them or a mixture of two or more of them can be used.
[0157] On the other hand, the mixing of the transition metal hydroxide and the lithium raw material can be carried out by solid-phase mixing such as jet milling, and the mixing ratio of the transition metal hydroxide as the precursor of the positive electrode active material and the lithium raw material can be determined within the range that satisfies the molar fractions of the respective components in the finally prepared positive electrode active material. More specifically, the transition metal hydroxide and the lithium raw material can be mixed so that the transition metal hydroxide and the lithium element in the lithium raw material are present in a molar ratio of 1:1.2 to 1:1.6.
[0158] On the other hand, although not necessary, during the mixing, in addition to the transition metal hydroxide and the lithium raw material, a raw material for doping a part of the transition metal and / or oxygen of the positive electrode active material can also be included. For example, during the mixing, the above-mentioned raw material containing M and / or the raw material containing X to be described later can also be mixed. In this case, the raw material containing X can be, for example, Na3PO4, K3PO4, Mg3(PO4)2, AlF3, NH4F, LiF, etc., but is not limited thereto. When a part of oxygen is replaced with the X element as described above, oxygen desorption and reaction with the electrolyte during charging / discharging of the secondary battery can be prevented.
[0159] In addition, the firing can be carried out at 750 °C to 1,050 °C, specifically 850 °C to 950 °C, and can be carried out for 5 to 30 hours, specifically 8 to 15 hours, but the firing temperature and duration are not limited thereto.
[0160] On the other hand, the transition metal hydroxide can be prepared by a method including the following steps:
[0161] Form an inactive atmosphere with a pH of 12 to 13 inside the reactor (S1),
[0162] Inject nitrogen and air with a volume ratio of 99.5:0.5 to 85.0:15.0 into the reactor to form an active atmosphere, add a transition metal solution containing Ni and Mn, and an alkaline solution, and carry out a coprecipitation reaction (S2) on the mixture under the condition that the pH is 10 to 11.
[0163] Hereinafter, a method for preparing a transition metal hydroxide according to the present invention will be described in detail step by step.
[0164] Step (S1)
[0165] Step (S1) is a step of forming an inert atmosphere inside the reactor and providing specific pH conditions before the coprecipitation reaction, and can be carried out by adding a solvent and an alkaline solution to the reactor, mixing the mixture to form an atmosphere with a pH of 12 to 13, and introducing an inert gas.
[0166] The solvent can be a polar solvent commonly used in the art, and can be, for example, water, an alcohol, or a mixture thereof.
[0167] There is no particular limitation on the inert gas as long as it is an inert gas commonly used in the art, and can be, for example, any one or more selected from nitrogen, argon, helium, and neon, and specifically can be nitrogen.
[0168] The alkaline solution is a precipitating agent and is used to adjust the pH in the reactor, and can be a hydroxide of an alkali metal or an alkaline earth metal, such as NaOH, KOH, or Ca(OH)2, its hydrate, or a combination thereof.
[0169] As another example, the alkaline solution can be used, for example, in the form of an aqueous solution. In this case, water or a mixture of water and an organic solvent (such as an alcohol) that can be uniformly mixed with water can be used as the solvent.
[0170] Step (S2)
[0171] Step (S2) is a step of coprecipitating transition metals to prepare a transition metal hydroxide, and can be carried out by the following steps: forming an active atmosphere again inside the reactor, adding a transition metal solution and an alkaline solution, and carrying out a coprecipitation reaction at a pH of 10 to 11.
[0172] Specifically, the active atmosphere can be provided by adding an inert gas and air in a volume ratio of 99.5:0.5 to 85.0:15.0 to the reactor to form a weak oxygen atmosphere. In this case, the inert gas can be as described above, and specifically can be nitrogen.
[0173] The preparation method according to the present invention is carried out through the following steps: during the coprecipitation reaction, a weakly oxygenated active atmosphere is formed in an inert atmosphere inside the reactor to form and grow narrow and short needle-shaped primary particles, so that pores can be uniformly formed up to the surface portion to obtain a transition metal hydroxide with a large specific surface area. Additionally, as a result, a positive electrode active material with a pore distribution up to the surface portion can be obtained by mixing the transition metal hydroxide with the above characteristics and a lithium raw material and firing the mixture, and the positive electrode active material, as an over-lithiated nickel-manganese type positive electrode active material, is favorable for lithium ion movement during charging / discharging, thereby having a reduced resistance and excellent capacity characteristics and life characteristics.
[0174] Additionally, the coprecipitation reaction can be carried out through the following steps: within 1 to 2 hours after adding the transition metal solution to the reactor, an alkaline solution is added to make the pH in the reactor reach 10 to 11 to initiate the reaction, and the reaction is continued for 20 to 50 hours while maintaining the pH at 10 to 11.
[0175] Additionally, the coprecipitation reaction can be carried out under stirring at a temperature of 40°C to 60°C, and there is no particular limitation on the stirring speed, but the stirring can be carried out at 100 rpm to 1,000 rpm to facilitate the improvement of the reaction speed.
[0176] The transition metal solution can be prepared by adding a transition metal raw material to a solvent, specifically water or a solvent mixture of water and an organic solvent that can be uniformly mixed with water (e.g., alcohol, etc.), or by mixing an aqueous solution of the transition metal raw material.
[0177] The transition metal raw material can be a sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide, or hydroxyoxide of a transition metal.
[0178] As a specific example, for instance, the Ni raw material can be a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or hydroxyoxide, more specifically Ni(OH)2, NiO, NiOOH, NiCO 3· 2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4·6H2O, nickel salts of fatty acids, nickel halides, or a combination thereof, but not limited thereto.
[0179] Additionally, for example, the Mn raw material can be a manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or hydroxyoxide, more specifically: manganese oxides such as Mn2O3, MnO2, and Mn3O4; manganese salts such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, or nickel salts of fatty acids; manganese hydroxyoxides; manganese chlorides, or a combination thereof, but not limited thereto.
[0180] As another example, the transition metal solution may further contain at least one selected from Zr, Al, Re, V, Co, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na, and Pt. In this case, the transition metal solution may further contain a raw material containing Zr, Al, Re, V, Co, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na, or Pt, and the raw material may be an acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or hydroxyoxide containing each of the above metals.
[0181] In addition, the content of Mn in the transition metal solution may be 50 mol% or more relative to the transition metal in the solution.
[0182] As another example, the transition metal solution does not contain Co.
[0183] The method for preparing the positive electrode active material according to an embodiment of the present invention may further include washing and drying after firing to remove lithium by-products. For example, the washing can be carried out by adding the prepared positive electrode active material to ultrapure water and stirring the mixture. In this case, the washing temperature may be 20°C or lower, specifically 10°C to 20°C, and the washing can be carried out for about 10 minutes to 1 hour. When the washing temperature and time satisfy the above ranges, the lithium by-products can be effectively removed.
[0184] Positive Electrode and Secondary Battery
[0185] The present invention provides a positive electrode including the above positive electrode active material, and a lithium secondary battery including the positive electrode.
[0186] The positive electrode according to an embodiment of the present invention includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. In this case, the positive electrode active material layer contains the positive electrode active material.
[0187] The positive electrode can be prepared according to a typical method for preparing a positive electrode, except that the above positive electrode active material is used. For example, the positive electrode can be prepared by the following steps: dissolving or dispersing the components constituting the positive electrode active material layer, such as the positive electrode active material, conductive material, and / or binder, in a solvent to prepare a positive electrode material mixture, coating the positive electrode material mixture on at least one surface of the positive electrode current collector, and then drying and rolling, or it can be prepared by casting the positive electrode material mixture on a separate support and then laminating the film separated from the support on the positive electrode current collector.
[0188] In this case, there is no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. Additionally, the positive electrode current collector typically may have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and non-woven fabric bodies.
[0189] A positive electrode active material layer containing the positive electrode active material according to the present invention and optionally further containing at least one of a conductive material and a binder is located on at least one surface of the current collector.
[0190] Relative to the total weight of the positive electrode active material layer, the content of the positive electrode active material can be 80% by weight to 99% by weight, more specifically 85% by weight to 98% by weight. When the content is within the above range, the positive electrode active material can exhibit excellent capacity characteristics.
[0191] The conductive material is used to impart conductivity to the electrode, and any conductive material can be used without particular limitation as long as it has electron conductivity and does not cause chemical changes in the battery to be constructed. Specific examples thereof may include: graphite, such as natural graphite or artificial graphite; carbonaceous materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking carbon black, and carbon fiber; powders of metals such as copper, nickel, aluminum, and silver or metal fibers; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one or a mixture of two or more thereof can be used. Relative to the total weight of the positive electrode active material layer, the content of the conductive material can be 1% by weight to 30% by weight.
[0192] In addition, the binder is used to improve the binding between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Specific examples thereof may include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride - hexafluoropropylene copolymer (PVDF - co - HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene - butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one or a mixture of two or more thereof can be used. Relative to the total weight of the positive electrode active material layer, the content of the binder can be 1% by weight to 30% by weight.
[0193] On the other hand, the solvent used in the preparation of the positive electrode material mixture can be a solvent commonly used in the art. As the solvent, for example, dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc. can be used alone or in combination. Considering the coating thickness, manufacturing yield, viscosity, etc. of the slurry, the amount of the solvent can be appropriately adjusted.
[0194] In addition, the lithium secondary battery according to the present invention includes a positive electrode, a negative electrode located opposite to the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. In this case, the positive electrode is the positive electrode according to the present invention described above.
[0195] On the other hand, the lithium secondary battery may optionally further include a battery case for accommodating the electrode assembly composed of the positive electrode, the negative electrode, and the separator, and a sealing member for sealing the battery case.
[0196] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector.
[0197] The negative electrode can be prepared according to a typical method for preparing a negative electrode known in the art. For example, the negative electrode can be prepared by the following steps: dissolving or dispersing the components constituting the negative electrode active material layer, such as a negative electrode active material, a conductive material, and / or a binder, in a solvent to prepare a negative electrode material mixture, coating the negative electrode material mixture on at least one surface of the negative electrode current collector, and then drying and rolling, or it can be prepared by casting the negative electrode material mixture on a separate support and then laminating the film separated from the support on the negative electrode current collector.
[0198] There is no particular limitation on the negative electrode current collector as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum cadmium alloy, etc. can be used. In addition, the negative electrode current collector usually can have a thickness of 3 μm to 500 μm, and as in the case of the positive electrode current collector, fine irregularities can be formed on the surface of the negative electrode current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam body, and a non-woven fabric body.
[0199] Compounds capable of reversibly inserting and extracting lithium can be used as the negative electrode active material. Specific examples thereof may include: carbonaceous materials, such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; (semi) metallic materials capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; (semi) metal oxides capable of doping and de-doping lithium, such as SiO v(0 < v < 2), SnO2, vanadium oxides, and lithium vanadium oxides; or a composite material containing (semi) metallic materials and carbonaceous materials, such as Si-C composite materials or Sn-C composite materials, and any one of them or a mixture of two or more of them can be used. Additionally, as the negative electrode active material, a lithium metal thin film can be used. Further, as the carbon material, low-crystalline carbon, high-crystalline carbon, etc. can all be used. Typical examples of low-crystalline carbon can be soft carbon and hard carbon, and typical examples of high-crystalline carbon can be irregular, planar, flaky, spherical, or fibrous natural graphite or artificial graphite, condensated graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microbeads, mesophase pitch, and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch.
[0200] In addition, the binder and the conductive material can be the same as those described above for the positive electrode.
[0201] On the other hand, in a secondary battery, the separator is for separating the negative electrode and the positive electrode and providing a migration path for lithium ions. Any separator can be used without particular limitation as long as it is commonly used as a separator in secondary batteries. In particular, a separator with high moisture retention ability for the electrolyte and low resistance to the migration of electrolyte ions is preferred. Specifically, a porous polymer membrane can be used, such as a porous polymer membrane prepared using polyolefin polymers such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or a laminated structure having two or more layers thereof. Additionally, typical porous non-woven fabrics can be used, such as non-woven fabrics formed from glass fibers with high melting points, polyethylene terephthalate fibers, etc. Furthermore, to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material can be used, and a separator having a single-layer or multi-layer structure can be optionally used.
[0202] On the other hand, the electrolyte can be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten-type inorganic electrolyte, etc., all of which can be used in the manufacture of secondary batteries, but are not limited thereto.
[0203] Specifically, the electrolyte can contain an organic solvent and a lithium salt.
[0204] Any organic solvent can be used without particular limitation as long as it can serve as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as the organic solvent, the following can be used: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol solvents such as ethanol and isopropyl alcohol; nitriles such as Ra-CN (where Ra is a linear, branched, or cyclic C2 to C20 hydrocarbon group and may contain double bonds, aromatic rings, or ether bonds); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane. Among these solvents, carbonate solvents are preferred, and more preferably a mixture of a cyclic carbonate (such as ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant and a linear carbonate compound (such as ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) having low viscosity, which can improve the charge / discharge performance of the battery. In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be excellent.
[0205] The lithium salt can be used without particular limitation as long as it is a compound capable of providing lithium ions used in the lithium secondary battery. Specifically, as the lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO 4、 LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. The lithium salt can be used in a concentration range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, thereby exhibiting excellent performance, and lithium ions can move effectively.
[0206] In the electrolyte, in order to improve the life characteristics of the battery, suppress the decrease in battery capacity, and improve the discharge capacity of the battery, one or more additives can also be included, such as: halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (poly)glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, etc. In this case, the content of the additive can be 0.1% by weight to 5% by weight based on the total weight of the electrolyte.
[0207] A secondary battery including the above-described positive electrode active material according to the present invention has excellent capacity characteristics and high-temperature stability, and thus can be advantageously applied to portable devices such as mobile phones, laptop computers, and digital cameras, as well as electric vehicles such as hybrid electric vehicles (HEVs).
[0208] In addition, the secondary battery according to the present invention can be used as a unit cell of a battery module, and the battery module can be applied to a battery pack. The battery module or the battery pack can be used as a power source for one or more medium and large-sized devices such as electric tools; electric vehicles such as electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); or power storage systems.
[0209] Examples
[0210] Hereinafter, examples of the present invention will be described in detail in a manner that enables those skilled in the art to easily implement the present invention. However, the present invention can be implemented in various different forms and is not limited to the embodiments described herein.
[0211] Example 1
[0212] (1) Preparation of transition metal hydroxide
[0213] NiSO4 and MnSO4 were mixed in deionized water at a molar ratio of Ni:Mn of 35:65 to prepare a 2.4 M transition metal aqueous solution.
[0214] 2.6 L of deionized water and 3.5 ml of a 25 wt% NaOH aqueous solution were added to a 10 L continuous stirred tank reactor, and the mixture was stirred at 150 rpm at a constant temperature of 50 °C to set the pH in the reactor to 12, and nitrogen was supplied at 2 L / min to remove dissolved oxygen inside the reactor and form a non-oxidizing atmosphere.
[0215] Thereafter, nitrogen and air in a volume ratio of 90:10 were introduced into the reactor while stirring at 1000 rpm to form a weak oxygen atmosphere, and the transition metal aqueous solution was continuously introduced into the reactor at 0.85 L / h. In this case, the NaOH aqueous solution was introduced into the reactor together with the transition metal aqueous solution so that the pH in the reactor reached 10 within 2 hours to initiate a coprecipitation reaction, and then the coprecipitation reaction was continued for 50 hours at a constant pH of 10. After the coprecipitation reaction was completed, the obtained transition metal hydroxide was separated, washed, and dried at 100 °C for 12 hours to prepare a transition metal hydroxide [Mn 0.65 Ni 0.35 (OH)2] as a precursor of the positive electrode active material.
[0216] (2) Preparation of the positive electrode active material
[0217] 50 g of the prepared transition metal hydroxide was mixed with 31.1 g of LiOH for 20 minutes using a mechanical homogenizer and heat-treated at 900 °C for 10 hours to prepare the positive electrode active material [0.63(LiMn 0.57 Ni 0.43 O2)·0.37(Li2MnO3)].
[0218] Example 2
[0219] For Example 1, the transition metal hydroxide [Mn 0.65 Ni 0.35 (OH)2] and the positive electrode active material [0.63(LiMn 0.57 Ni 0.43 O2)·0.37(Li2MnO3)] were prepared in the same manner as in Example 1, except that nitrogen and air were added in a volume ratio of 95:5 to form a weak oxygen atmosphere.
[0220] Example 3
[0221] For Example 1, the transition metal hydroxide [Mn 0.65 Ni 0.35 (OH)2] and the positive electrode active material [0.63(LiMn 0.57 Ni 0.43 O2)·0.37(Li2MnO3)] were prepared in the same manner as in Example 1, except that nitrogen and air were added in a volume ratio of 99:1 to form a weak oxygen atmosphere.
[0222] Comparative Example 1
[0223] (1) Preparation of the transition metal hydroxide
[0224] NiSO4 and MnSO4 were mixed in deionized water at a Ni:Mn molar ratio of 35:65 to prepare a 2.4 M transition metal aqueous solution.
[0225] 2.6 L of deionized water and 3.5 ml of a 25 wt% NaOH aqueous solution were added to a 10 L continuous stirred tank reactor and stirred at 150 rpm at a constant temperature of 50 °C to set the pH in the reactor to 12, and nitrogen was supplied at 2 L / min to remove the dissolved oxygen inside the reactor and form a non-oxidizing atmosphere.
[0226] Thereafter, an aqueous solution of transition metal was continuously introduced into the reactor at a rate of 0.85 L / h. In this case, an aqueous solution of NaOH was introduced into the reactor together with the aqueous solution of transition metal so that the pH in the reactor reached 10 within 2 hours to initiate the coprecipitation reaction, and then the coprecipitation reaction was continued for 50 hours at a constant pH of 10. After the coprecipitation reaction was completed, the obtained transition metal hydroxide was separated, washed, and dried at 100 °C for 12 hours to prepare a transition metal hydroxide [Mn 0.65 Ni 0.35 (OH)2] as a precursor of the positive electrode active material.
[0227] (2) Preparation of the positive electrode active material
[0228] 50 g of the prepared transition metal hydroxide was mixed with 31.1 g of LiOH using a mechanical homogenizer for 20 minutes and heat-treated at 900 °C for 10 hours to prepare a positive electrode active material [0.63(LiMn 0.57 Ni 0.43 O2)·0.37(Li2MnO3)].
[0229] Comparative Example 2
[0230] (1) Preparation of the transition metal hydroxide
[0231] NiSO4 and MnSO4 were mixed in deionized water at a molar ratio of Ni:Mn of 35:65 to prepare a 2.4 M aqueous solution of transition metal.
[0232] 2.6 L of deionized water and 3.5 ml of an aqueous solution of NaOH with a concentration of 25 wt% were added to a 10 L continuously stirred tank reactor, and the mixture was stirred at a constant temperature of 50 °C at 150 rpm to set the pH in the reactor to 12, and nitrogen was supplied at a rate of 2 L / min to remove the dissolved oxygen inside the reactor and form a non-oxidizing atmosphere.
[0233] Thereafter, air was introduced into the reactor while stirring at 1000 rpm to form an oxygen atmosphere, and an aqueous solution of transition metal was continuously introduced into the reactor at a rate of 0.85 L / h. In this case, an aqueous solution of NaOH was introduced into the reactor together with the aqueous solution of transition metal so that the pH in the reactor reached 10 within 2 hours to initiate the coprecipitation reaction, and then the coprecipitation reaction was continued for 50 hours at a constant pH of 10. After the coprecipitation reaction was completed, the obtained transition metal hydroxide was separated, washed, and dried at 100 °C for 12 hours to prepare a transition metal hydroxide [Mn 0.65 Ni 0.35 (OH)2] as a precursor of the positive electrode active material.
[0234] (2) Preparation of the positive electrode active material
[0235] The prepared 50 g of transition metal hydroxide was mixed with 31.1 g of LiOH using a mechanical homogenizer for 20 minutes and heat-treated at 900 °C for 10 hours to prepare a positive electrode active material [0.63(LiMn 0.57 Ni 0.43 O2)·0.37(Li2MnO3)].
[0236] Comparative Example 3
[0237] For Example 1, transition metal hydroxide [Mn 0.65 Ni 0.35 (OH)2] and positive electrode active material [0.63(LiMn 0.57 Ni 0.43 O2)·0.37(Li2MnO3)] were prepared in the same manner as in Example 1, except that nitrogen and air were added in a volume ratio of 80:20 to form a weak oxygen atmosphere.
[0238] Experimental Example 1
[0239] The surface porosity of each positive electrode active material prepared in the examples and comparative examples was analyzed, and the results are shown in Figures 1 to 6 and Table 1.
[0240] The pore shape on the cross-section of each positive electrode active material was observed using SEM (Quanta FEG 250, manufactured by PHILIPS) under the following conditions.
[0241] High voltage: 10,000 kV
[0242] Chamber pressure: 9.0×10 -5 mbar
[0243] Gun pressure: 6.85×10 -10 mbar
[0244] Emission current: 165 μA
[0245] WD: 10 mm
[0246] Beam spot size: 3.0
[0247] Stage bias voltage: 4000 V
[0248] In addition, the porosity of the surface part was measured according to the schematic diagram shown in Fig. 7.
[0249] Specifically, particles on each cross-section (Fig. 7(a)) are selected to obtain a particle contour and the unnecessary background part is removed, and the inner and surface parts are distinguished (Fig. 7(b)), so that the surface porosity A is measured using the image processing program ImageJ. In this case, the inner part on the cross-section is the region formed by connecting the points at a distance of 1 / 2 from the center to the outermost surface on the cross-section of the positive electrode active material (see Fig. 7(b)).
[0250] First, using ImageJ, the area ratio A1 occupied by the surface part other than pores with respect to the total area of the image and the area ratio A2 other than the pores in the surface part with respect to the total area of the image are obtained (Fig. 7(c) and (d)). Thereafter, the area ratio A2 other than the pores in the surface part is subtracted from the total area 100 (100 - A2) to obtain the area ratio P of the pores in the surface part A . The area ratio A1 occupied by the surface part and the area ratio P of the pores in the surface part A are added together to calculate the area ratio S of the surface part A .
[0251] Thereafter, the surface porosity is calculated by the following mathematical formula 1.
[0252] [Mathematical formula 1]
[0253] A(%) = [P A / S A ×100
[0254] In the above mathematical formula 1,
[0255] P A represents the area ratio of the pores in the surface part on the cross-section of the positive electrode active material,
[0256] S A is the area ratio of the surface part on the cross-section of the positive electrode active material,
[0257] the inner part of the cross-section of the positive electrode active material is the region formed by connecting the points at a distance of 1 / 2 from the center to the outermost surface on the cross-section of the positive electrode active material, and
[0258] the surface part on the cross-section of the positive electrode active material is the region other than the inner part.
[0259] In addition, a cross-section of the positive electrode active material is obtained using SEM (Quanta FEG 250, PHILIPS), 30 particles are selected from this cross-section, and the area ratio P of the pores in the surface part of each of the 30 particles is obtained through the above process Ai (where i is an integer from 1 to 30) and the area ratio S of the surface part Ai(where i is an integer from 1 to 30), and the surface porosity A of 30 particles is obtained by the above mathematical formula 1 i (where i is an integer from 1 to 30), and then the average value thereof is also provided as the surface porosity A' of each positive electrode active material (see the following mathematical formula 2). In this case, Comparative Example 3 shows 20 particles.
[0260] [Mathematical formula 2]
[0261]
[0262] (where n is the integer 30)
[0263]
[0264] Figures 1 to 6 It is shown that the pores of the positive electrode active materials of Examples 1 to 3 are uniformly distributed on the surface portion. Table 1 shows that the surface porosities of the positive electrode active materials of Examples 1 to 3 are 1% to 30%. On the other hand, it was confirmed that the surface porosities of the positive electrode active materials of Comparative Examples 1 and 2 are less than 1%. In addition, it was confirmed that the standard deviation between the surface porosity A and the surface porosity A' (average value of 30 particles) of Examples 1 to 3 is 2 or less, and thus a uniform porosity with almost no deviation between the particles forming each positive electrode active material is obtained.
[0265] On the other hand, the surface porosity of Comparative Example 3 is greater than 30%, and thus serious particle breakage occurs. Accordingly, it is impossible to fabricate a positive electrode and evaluate battery characteristics, which will be described later. In addition, when calculating the surface porosity A' of 20 particles, the deviation of the surface porosity varying with particles in Comparative Example 3 is greater than 10, indicating that the surface porosities of the respective particles are not uniform.
[0266] Experimental Example 2
[0267] Each positive electrode active material prepared in the examples and comparative examples was used to fabricate a positive electrode and a battery, and then the battery performance was evaluated.
[0268] (1) Fabrication of positive electrode
[0269] Each of the above-prepared positive electrode active materials, carbon black conductive material, and PVdF binder was mixed in an N-methylpyrrolidone solvent at a weight ratio of 92.5:3.0:4.5 to prepare a positive electrode material mixture (viscosity: 5000 mPa·s). The mixture was coated on one surface of an aluminum current collector, dried at 130°C, and then rolled to prepare a positive electrode.
[0270] (2) Fabrication of battery
[0271] Lithium metal was used as the negative electrode.
[0272] A porous polyethylene separator was inserted between the above-prepared positive and negative electrodes to prepare an electrode assembly, and the electrode assembly was placed inside a battery case. Thereafter, an electrolyte was injected into the case to fabricate a lithium secondary battery. In this case, the electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.0 M in an organic solvent formed by ethylene carbonate / ethyl methyl carbonate (EC / EMC, mixed volume ratio = 3 / 7), and adding 3 wt% of fluoroethylene carbonate (FEC) and 0.5 wt% of LiBF4 as additives.
[0273] Each of the lithium secondary battery half-cells fabricated as above was charged at 25 °C in a CCCV mode at 0.1C until 4.7 V and discharged at a constant current of 0.1C until 2.0 V to measure the initial charge / discharge capacity. In addition, the capacity retention rate was determined after charging and discharging at 0.1C 30 times. The results are shown in Table 2 below.
[0274] In addition, the initial resistance and the resistance increase rate were measured by the change in the voltage amount at the initial 60 seconds of discharge in each cycle of each half-cell.
[0275]
[0276] As shown in Table 2, it was confirmed that Examples 1 to 3 were significantly superior to Comparative Examples 1 and 2 in terms of the initial charge / discharge capacity and the capacity retention rate, and Examples 1 to 3 showed significantly improved initial resistance and resistance increase rate. On the other hand, the surface porosity of the positive electrode active material in Comparative Example 3 was too high, resulting in a low particle density. As a result, most of the particles were broken during the fabrication of the electrode, and thus the battery could not be fabricated.
Claims
1. A positive electrode active material, the positive electrode active material is represented by the following chemical formula 1 and is formed of polycrystalline particles, the polycrystalline particles are composed of secondary particles in which primary particles are agglomerated, The surface porosity A defined by the following mathematical formula 1 is 1% to 30%, [Chemical formula 1] x[LiMn p Ni (1-p-q-r) Co q M 1 r O2]·(1-x)[Li2Mn s M 2 (1-s) O3] Wherein in the above chemical formula 1, M 1 and M 2 Each is independently one selected from Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na and Pt, and Meet 0.500 <x<0.800、0.450<p<0.650、0≤q≤0.025、0≤r≤0.100、0.900≤s≤1.000, [Mathematical formula 1] A(%)=[P A / S A ]×100 In the above mathematical formula 1, P A represents the area ratio of pores in the surface portion on the cross section of the positive electrode active material, S A is the area ratio of the surface portion on the cross section of the positive electrode active material, The interior of the cross section of the positive electrode active material is a region formed by connecting points at 1 / 2 of the distance from the center of the cross section of the positive electrode active material to the outermost surface of the cross section of the positive electrode active material, and The surface portion on the cross section of the positive electrode active material is a region excluding the inner portion. 2 . The positive electrode active material according to claim 1 , wherein the surface porosity A is 2% to 20%. 3 . The positive electrode active material according to claim 1 , wherein the positive electrode active material does not contain Co.
4. The positive electrode active material according to claim 1, wherein the positive electrode active material is represented by the following chemical formula 1-1: [Chemical formula 1-1] x[LiMn p Ni (1-p-r) M 1 r O2]·(1-x)[Li2Mn s M 2 (1-s) O3] In the above chemical formula 1-1, M 1 and M 2 Each is independently one selected from Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na and Pt, and Meets 0.55 <x<0.70、0.52<p<0.58、0≤r≤0.10、0.90≤s≤1.00。 5. The positive electrode active material according to claim 1, wherein the average particle size D of the positive electrode active material is 50 3 μm to 12 μm.
6. A method for preparing a positive electrode active material represented by the following chemical formula 1, the method comprising the steps of: mixing a transition metal hydroxide with a lithium raw material and firing, The transition metal hydroxide is prepared by the following steps: An inert atmosphere with a pH of 12 to 13 is formed inside the reactor (S1); Nitrogen and air in a volume ratio of 99.5:0.5 to 85.0:15.0 are injected into the reactor to form an active atmosphere, a transition metal solution containing Ni and Mn, and an alkaline solution are added, and the mixture is subjected to a coprecipitation reaction under a pH of 10 to 11 (S2), [Chemical formula 1] x[LiMn p Ni (1-p-q-r) Co q M 2 r O2]·(1-x)[Li2Mn s M 1 (1-s) O3] Wherein in the above chemical formula 1, M 1 and M 2 Each is independently one selected from Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na and Pt, and Meet 0.500 <x<0.800、0.450<p<0.650、0≤q≤0.025、0≤r≤0.100、0.900≤s≤1.000。 7. The method according to claim 6, wherein the step (S1) is performed by adding a solvent and an alkaline solution to a reactor and mixing to form an atmosphere having a pH of 12 to 13, and then introducing an inert gas.
8. The method according to claim 6, wherein in the step (S2), the coprecipitation reaction is carried out by the following steps: adding the alkaline solution within 1 to 2 hours after adding the transition metal solution to the reactor so that the pH in the reactor reaches 10 to 11 to initiate the reaction, and The reaction is continued for 20 to 50 hours while maintaining the pH at 10 to 11.
9. The method according to claim 6, wherein the content of Mn in the transition metal of the transition metal hydroxide is 50 mol % or more.
10. The method according to claim 6, wherein the transition metal hydroxide does not contain Co.
11. The method according to claim 6, wherein the transition metal hydroxide is mixed with the lithium raw material so that the transition metal hydroxide and the lithium element in the lithium raw material are present in a molar ratio of 1:1.2 to 1:1.
6.
12. A positive electrode, comprising: Current collector; and a positive electrode active material layer disposed on at least one surface of the current collector, The positive electrode active material layer comprises the positive electrode active material according to claim 1 .
13. A lithium secondary battery, comprising: The positive electrode according to claim 12; negative electrode; a separator between the positive electrode and the negative electrode; and Electrolytes.
Citation Information
Patent Citations
Porous tungsten trioxide coated modified positive electrode material and preparation method thereof
CN110112388A
Fixing apparatus for pipe support
KR1020230011790A